Clitoria ternatea Flower Extract Mediated Synthesis of Ni-Doped Hydroxyapatite as Photocatalyst, Antibacterial, and Drug Delivery Agent for Anticancer Drug - Fatimah, Is; Nurlaela, Nunung; Fauziyyah, Anas Zahra; Sagadevan, Suresh; Hidayat, Habibi; Haneef, Mehru Nisha Muhamad; Daud, Muhammad Fauzi; Kamari, Azlan; Oh, Won-Chun (Science and Technology Indonesia, 2025)
In the present study, green synthesis of nickel-doped hydroxyapatite using Clitoria ternatea flower extract, and activity testing as photocatalyst, antibacterial agent and drug delivery agent were performed. Synthesis was conducted by hydrothermal treatment of co-precipitated precursors previously mediated with the extract. As drug delivery agent, immobilization of 5-fluorouracil (5FU) onto the prepared sample was performed by spray-drying method. Physicochemical characterization techniques of X-ray diffraction, UV-Visible Diffuse Reflectance Spectrophotometry, transmission electron microscopy, Raman and Fourier-Transform Infra-red spectroscopy were performed to determine the structural and surface properties of material. Photocatalytic activity evaluation for tetracycline removal showed that material has capability to reduce concentration by photocatalytic degradation and photocatalytic oxidation. The degradation efficiency of material was 83.78%. The prepared material exhibited a significant activity against Staphylococcus aureus and Escherichia coli bacteria. The material also expressed the potency as a drug-delivery agent of 5-fluorouracil as shown by the reduced CT26 cell viability of more than 85% during 48 hours.